Concanavalin a and wheat germ agglutinin receptors on dictyostelium: Their visualization by scanning electron microscopy with microspheres - Molday, R (The Rockefeller University Press, 1976)
The cellular slime mold, Dictyostelium discoideum, is a convenient model for studying cellular interactions during development. Evidence that specific cell surface components are involved in cellular interactions during its development has been obtained by Gerisch and co-workers (1, 2) using immunological techniques. Smart and Hynes (3) have shown that a cell surface protein can be iodinated on cells in aggregation phase, but not in vegetative phase, by the lactoperoxidase procedure. Recently, McMahon et al. (4), and Hoffman and McMahon have demonstrated, by SDS gel electrophoresis, considerable differences in cell surface proteins and glycoproteins of plasma membranes isolated from cells at different stages of development. Plant lectins have also been used to monitor changes in cell surface properties of D. discoideum cells during development. Weeks and co-workers (5, 6) have detected differences in the binding and agglutination of cells by concanavalin A (Con A). Gillette and Filosa (7) have shown that Con A inhibits cell aggregation and prematurely induces cyclic AMP phosphodiesterase. Capping of Con A receptors has also been reported (8). Reitherman et al. (9) have recently reported that agglutination of cells by several plant lectins and the slime mold agglutination, discoidin, changes during development. Such studies indicate that differences in surface properties exist for cells at various stages of development. However, owing to the uncertainties in the factors which contribute to lectin-induced cell agglutination (10), the molecular basis for these observations remain to be determined. In this study, we have used microspheres (11-14) coupled to either Con A or wheat germ agglutinin (WGA) as visual markers to study by scanning electron microscopy the topographical distribution of lectin receptors on D. discoideum cells fixed at different stages of development. We also describe the effect of labeling on the distribution of lectin receptors and on the morphology of the cell surface.